Redescription of Lepidodactylus flaviocularis (Squamata: Gekkonidae), with the description of a new species from Makira Island, Solomon Islands - Kraus, Fred (Zootaxa, 2023)
Several species of geckos of the genus Lepidodactylus are endemic to the Solomon Islands and very poorly known. I redescribe one of these, L. flaviocularis, from Guadalcanal, based on examination of a second, newly obtained specimen and quantification of diagnostically useful features of the digits. I also describe a closely related new species from nearby Makira Island in the southern Solomon Islands. Both species are distinguished by their large number of undivided subdigital lamellae, extensive toe webbing, and a continuous row of enlarged precloacal/femoral scales. The new species is distinguished from L. flaviocularis by a number of scalational features and the color of the circumorbial scales. Both species are inhabitants of interior forest, and it remains uncertain whether they are naturally rare, rare due to interactions with invasive species, or simply have cryptic ecological habits, though the last seems most likely. Current evidence for both species is consistent with the taxon-cycle hypothesis, which posits ecological displacement to inland habitats of ancient island inhabitants by newer colonizers, but this remains to be critically tested. The limited pool of specimens available for both species necessitates assessing the IUCN conservation status of each as Data Deficient.